Cost efficiency of retrofit measures for typical masonry houses in Kosovo - Bajraktari, Egzon (2019)
A major challenge our society faces today is the energy consumption of buildings. Building stock is responsible for about 40% of energy consumption worldwide. The same applies to Kosovo, where a large number of houses are poorly weatherized and inefficient in terms of energy consumption. Most of the energy consumption in the household sector in Kosovo is dedicated to the needs for heating purposes. Furthermore, many of these houses use wood or coal for heating, releasing a lot of gases in the air and so contributing to increased air pollution both indoors and outdoors. The Faculty of Civil Engineering and Architecture at the University of Prishtina ?Hasan Prishtina? aims to address the issue of energy efficiency for these houses. Specifically, in this study, we intend to evaluate various retrofit measures applicable in the country for typical masonry houses and identify the cost-efficient solution. This paper reports the initial results of the study and discusses related challenges.